Determination of α‐Lipoic acid on a Pyrolytic Graphite Electrode Modified with Cobalt Phthalocyanine. Issue 10 (15th September 2014) - Ferreira, Ana Paula M.; dos Santos Pereira, Laise N.; da Silva, Iranaldo Santos; Tanaka, Sônia M. C. N.; Tanaka, Auro A.; Angnes, Lúcio
Abstract In this work voltammetric techniques were explored for quantification of α‐Lipoic acid (ALA) using a pyrolytic graphite electrode modified with cobalt phthalocyanine. Cyclic voltammograms recorded in phosphate buffer solution containing 1×10−3 mol L−1 of ALA presented an oxidation peak located at +0.8 V vs. SCE. The modification of the electrode produced a 100 mV shift of the onset oxidation potential to less positive value and a substantial increase in the ALA oxidation current. Among the voltammetric techniques explored, differential pulse voltammetry showed the best performance for quantifications of the analyte in low concentrations. Limits of detection and quantification of ALA obtained corresponds to 3.4×10−9 mol L−1 and 1.2×10−8 mol L−1, respectively.